Epidemiological Aspects of Cutaneous Leishmaniasis in Yazd Province within 2004-2013 - Hadis Barati; Mohamad Hasan Lotfi; Gholamali Mozafari; Hamidreza Dehghan; Mohamad Barati; Aliakbar Tajfirouzeh (Shahid Sadoughi University of Medical Sciences, 2016)
Abstract Introduction: Cutaneous leishmaniasis is recognized as one of the important neglected parasitic diseases worldwide. The present study aimed to determine the epidemiological patterns of cutaneous leishmaniasis in a period of ten years in Yazd province in Iran. Materials & Methods: This ecological study was performed on 5784 recorded cases within 2004-2013in health centers in Yazd. Meteorological data including maximum and minimum temperature, relative humidity and rainfall, received from Yazd Meteorological Organization. In order to analyze the study data, descriptive statistics, linear regression, spearman correlation and delay time were applied. Results: Out of a total of 5784 cases of cutaneous leishmaniasis, the most cases were observed among males (61.3%). The majority of cases were reportedin cities of Khatam, Yazd and Bafgh, respectively. The maximum incidence was observed in October in the autum. The correlation results between disease incidence and climatic factors revealed a weak correlation in regard with the temperature, whereas no significant correlation was observed with respect to the mean relative humidity and rainfall. Furthermore, the results of correlation analysis with a time delay of 9, 10, 11 months demonstrated that the disease incidence has a relatively strong negative correlation with the temperature parameters as well as a relatively strong positive correlation with the relative humidity and precipitation. Conclusion: Regarding the relationship between these three climatic factors with cutaneous leishmaniasis in Yazd province, we recommended climatic and environmental factors affecting disease to be measures in this area.